Initial practice of left atrial appendage closure device in Japan; single-center experience. Issue 6 (June 2022) - Fukunaga, Masato; Isotani, Akihiro; Shirai, Shinichi; Murakami, Naoto; Nakamura, Miho; Morinaga, Takashi; Ishizu, Kenichi; Kitano, Kazuki; Kataoka, Tatsuhiro; Hayashi, Masaomi; Hiroshima, Kenichi; Ando, Kenji
Highlights: The left atrial appendage closure (LAAC) has recently been introduced in Japan. The real-world data on LAAC in Japanese patients are scarce. The initial experience showed a high success rate but high post-procedural bleeding. The optimal antithrombotic regimens considering each background are warranted. Abstract: Background: The left atrial appendage closure (LAAC) device for patients with nonvalvular atrial fibrillation (NVAF) has recently been introduced in Japan. However, clinical data of Japanese patients are insufficient. Methods: In this single-center study, 55 consecutive patients (mean age, 74 years) who received LAAC therapy from September 2019 to December 2020 were analyzed. The WATCHMAN implant procedure (Boston Scientific, St. Paul, MN, USA) was performed under transesophageal echocardiography and general anesthesia for all cases. Results: The baseline CHA2 DS2 -VASc score was 4.6 ± 1.4, and the baseline HAS-BLED score was 3.8 ± 0.9. All procedures (98.2%) were successful, except for one, and no procedure-related complications were observed. After the procedures, various antithrombotic regimens were employed according to the bleeding risk of each patient; warfarin was used in 27 patients (49%), direct oral anticoagulants (DOACs) were used in 22 patients (40%), and dual antiplatelet therapy (DAPT) was employed in 6 patients. During a mean follow-up of 360 days, three cases of device-related thrombus (DRT) were detected. One DRT case was related to ischemic stroke. Nine patients had major bleeding during follow-up: two patients received DOACs, six patients received DAPT, and one patient received aspirin. Conclusions: In this initial Japanese experience, LAAC therapy for high bleeding risk patients with NVAF seems feasible. Optimal antithrombotic regimens are warranted for better clinical outcomes. Graphical abstract: Image, graphical abstract